IKLIM USAHA INDUSTRI PENGOLAHAN BIJI KAKAO - Firman Mutakin; Tumpal Sihaloho (Buletin Ilmiah Litbang Perdagangan, 2007)
Indonesia is one among three major producers of cocoa beans. Nevertheless, industrial performance of cocoa beans industrial process bearish for the past few years. The purposes of this research are to analyse policies related to development the cocoa processing industry as well as analizing factor which cause low quality of cocoa beans. Factors that caused an uncondusif business climate on cocoa beans industry ar among of hers; high administrative fee in form of tax and entry charges for raw material that caused and increase in production cost structure of the industrial process of the cocoa beans, The low quality of the cocoa benas itself resulted from the un willingness of the farmers to ferment their products, ages of plantswhich more that its productive age and caused small beans producted, mixture between high quality and low quality beans and bugs infection of cocoa plants.